From Brand Vision to Brand Evaluation The strategic process of growing and strengthening Brands - de Chernatony, Leslie (New York : Routledge Florence : Taylor & Francis Group [Distributor], 2010)
Annotation Seeing the world's biggest brands gain ground over the world's markets, you can't deny that the 25,000 students in the UK studying marketing will never understand their subject without knowing how branding works. This is THE key scholarly text in this crucial topic, an already hugely respected title and big seller in the field. It follows on from the introductory textbook Creating Powerful Brands, and comes highly illustrated with real examples of influential marketing campaigns. This is the book that will take students to the next level with the skills to develop and implement their own branding strategy.
College Audience